ANALYSIS OF SLOPES STABILITY WITH CANTILEVER RETAINING WALLS AND GEOTEXTILE STRENGTHENING ON LIWA CROSS ROAD - INTERSECTION OF KEMALA MOUNTAIN KM. 268 + 550 - Saputra, Septian Adi; Adha, Idharmahadi; Hadi, Yohanes Martono (Universitas Lampung, 2017)
Liwa Cross Roads – Intersection of Kemala Mount KM.268 + 550 is located on the hills of TNBBS Lampung which geographic conditions consists of cliffs and ravines are quite steep, so prone to sliding. This is certainly very harmful to the building and the road users around the slopes so that necessary alternative solutions that could make the slopes safe from the danger of landslides. One way is to build reinforcement construction on a slope such as geotextiles and cantilever retaining wall. In analyzing of the slope stability used a computer program, that is SLOPE/W, is used to calculate the safety factor accurately in a short time. Existing slope stability analys with the program SLOPE/W Bishop methods in wet and dry conditions obtained value of safety factor 0.433 and 0.4. These results prove the structure of the slopes is not safe, it is needed solutions to handle slope sliding that has a stable numerical secure slope value by using woven geotextile reinforcement by the number of 16 layers, tensile capacity 200 kN/m, cohesion 3 kPa and the friction angle of the soil 38o, vertical distance 2 m and a cantilever concrete retaining wall that has a height 15 m with a specific gravity 25 kN/m3, the compressive strength of concrete plans (f'c) 30 MPa and a tensile strength steel (fy) 400 MPa. Pile soil used to improve slope geometry made to reduce the slope. The results of slope sliding stability analysis, reinforced with geotextile using SLOPE/W obtained value of safety factor 1,332, while reinforced with cantilevered retaining wall at 1.852. For the analysis of external stability by geotextiles strengthening obtained bolsters safety factor 5.9479, shear stability 3.3531 and carrying capacity 3.4815, while the cantilevered retaining wall reinforcement obtained stability bolsters safety factor 6.0643, shear stability 2.2346 and carrying capacity 3.1828. Key words: Slope stability, stability of retaining walls, Geotextile, SLOPE/W.